2004
DOI: 10.1300/j045v18n03_05
|View full text |Cite
|
Sign up to set email alerts
|

What Street People Reported About Service Access and Drug Treatment

Abstract: This study presents the perceptions of a sample of homeless people, living on the streets, in Allegheny County, Pennsylvania. Questions were asked that elicited their opinions about drug addiction, housing and treatment needs. Two-thirds of the 225 persons interviewed in 2000 and 2001 reported that they were not eligible for treatment or housing. Forty-two percent of those who received treatment for substance use disorders reported that their treatment was ineffective because aftercare and residential supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Similar to research evidence participants in this study indicated that knowledge and training of frontline staff, including training regarding specific populations (Freund & Hawkins, 2004;Harris & Katz, 2009), were key to improved service delivery. They suggested that education and awareness of the homeless experience would produce more relevant programming: I think the ones who are high up in those buildings should actually go in and see the homeless.…”
Section: Agency Accountabilitysupporting
confidence: 76%
“…Similar to research evidence participants in this study indicated that knowledge and training of frontline staff, including training regarding specific populations (Freund & Hawkins, 2004;Harris & Katz, 2009), were key to improved service delivery. They suggested that education and awareness of the homeless experience would produce more relevant programming: I think the ones who are high up in those buildings should actually go in and see the homeless.…”
Section: Agency Accountabilitysupporting
confidence: 76%
“…Moreover, our finding that homeless and drug-bingeing participants were significantly more likely to encounter such barriers reveals that important disparities exist in which street youth are successfully able to navigate the system of addiction treatment services. Policymakers might carefully consider how to ensure that the services they make available to drug users are made equally accessible to homeless youth; they might consider, for example, the provision of housing during treatment for those who need it, as has been suggested previously (Freund and Hawkins, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…The majority of these relate to administrative policy and the general quality of care provided by the clinicians and other staff. Abstinence requirements, medication requirements, extensive bureaucracy, religious requirements, and restrictive eligibility criteria are among the major administrative hurdles that homeless individuals face (Bhui et al, 2006; Freund & Hawkins, 2004; Tsemberis, Moran, Shinn, Asmussen, & Shern 2003). Additional programmatic barriers include long waiting times, not knowing where to go, language barriers, feeling stigmatized by staff, high staff turnover, and overall bad experiences with providers (Bhui et al, 2006; Flores, Abreu, Oltvar, & Kastner, 1998; Lewis, Andersen, & Gelberg, 2003; Swick, 2006; Wilde et al, 2004).…”
Section: Behavioral Model For Vulnerable Populationsmentioning
confidence: 99%